Assessment of Heavy Metal Contamination in Mangrove Habitats of Crude Oil Exploration and Artisanal Refining Sites in Degema Oilfield - Okwakpam, Ikechi Omenihu; Barango, Sobere Lloyd; Onugha, Augustine Chimeebere (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
The study assessed the heavy mental contents of mangrove habitat in selected crude oil exploration sites and an artisanal refining site in Degema Oilfield Rivers State. The study adopted the true-experimental design on twelve (12) sampling points out of which eight (8) soil samples were from the Crude Oil Exploration Site (COES), two (2) soil samples from Artisanal Refining Site (ARS), and two (2) soil samples as the Control were randomly collected in triplicates and composited. The data collected was analyzed using mean and Analysis of Variance (ANOVA). The study revealed that: Cadmium (Cd) concentration (2.80 mg/L) at Bukuma community was significantly higher than all other sampling points. Also, Pb, Cd, Fe, and Cu concentrations of 0.49 mg/L, 1.34 mg/L, 21.75 mg/L, and44.64 mg/L respectively at the artisanal refining site are significantly higher than the control (0.07 mg/L), WHO (2017) limit of 3.0, 0.01, 0.003, and 0.003 for Pb, Cd, Fe, and Cu respectively in soil. Hence, the result concluded that Crude oil extraction increases the concentration of harmful heavy metals in mangroves, highlighting the need for targeted interventions to reduce pollution and human health effects. The study recommended that The Nigeria Environmental Society should collaborate with governments to monitor companies' compliance with operating standards to reduce the discharge of untreated effluents containing heavy metals that harm mangroves, biodiversity, and contaminate food and water sources as well as harm human health.